Advances in Biosynthesis, Regulation, and Function of Apple Cuticular Wax - Zhang, Ya-Li; You, Chun-Xiang; Li, Yuan-Yuan; Hao, Yu-Jin (Frontiers in Plant Science, 2020)
A layer of cuticular wax is deposited on the surface of terrestrial plants, which reduces the damage caused by environmental stress and maintains growth in a relatively stable internal environment. Apple cuticular wax is an important part of the fruit epidermis that plays an essential role in apple development and storage. The formation of cuticular wax has been described at the transcriptional, post-transcriptional, and translational levels in Arabidopsis, whereas less research has been performed on apple cuticular wax. Here, we provide a brief overview of how apple cuticular wax is formed, as well as its structure, composition, and function. An association among the environment, genes, and apple cuticular wax deposition was revealed. Cuticular wax prevents fruit rust from occurring on apple. Taken together, a detailed understanding of apple cuticular wax is discussed. The results will act as a reference for extending the storage period and the increasing the commodity value of apple.